2018
DOI: 10.4103/ua.ua_4_17
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the international prostate symptoms scores for patients with lower urinary tract symptoms: A descriptive cross-sectional study

Abstract: Background:Lower urinary tract symptoms (LUTSs) can significantly reduce men's quality of life and may point to serious pathology of the urogenital tract. This study aimed at finding predictors of symptoms score on the International Prostate Symptom Score (IPSS) for patients with LUTS.Materials and Methods:The study was cross-sectional conducted among 225 Ghanaian men visiting the urology clinic at Komfo Anokye Teaching Hospital. Trained interviewers used the IPSS, which adds a quality of life question to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In recent years, many researches have shown the correlation between IPSS and different factors associated with BPH; such as age, prostate volume, peak flow rate, post-void residual urine and clinical bladder outlet obstruction [7][8][9] . All of the studies cited above have shown that higher IPSS correlated with many factors, which indicated more severity of BPH symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, many researches have shown the correlation between IPSS and different factors associated with BPH; such as age, prostate volume, peak flow rate, post-void residual urine and clinical bladder outlet obstruction [7][8][9] . All of the studies cited above have shown that higher IPSS correlated with many factors, which indicated more severity of BPH symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The Thai version of the International Prostate Symptom Score (IPSS-Th) is reliable and can be used in the same manner as the English version 5 . There are many studies that demonstrate the correlation between IPSS and factors associated with BPH; for example, quality of life 6 , age 7,8 , prostate-specific antigen (PSA) 8 , prostate volume 7,8 , post void volume 7 and peak flow rate 7,9 . However, only a limited number of reports emphasize the correlation between IPSS and complications of BPH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation